A Machine Learning Approach on Chest X-Rays for Pediatric Pneumonia Detection - Barakat, Natali Imad (2022)
A Master of Science thesis in Engineering Systems Management by Natali Imad Barakat entitled, “A Machine Learning Approach on Chest X-Rays for Pediatric Pneumonia Detection”, submitted in June 2022. Thesis advisor is Dr. Mahmoud Awad and thesis co-advisor is Dr. Bassam Abu-Nabah. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).